Analysis of the CSFs affecting project execution: a case application. (7th June 2018) - Lin, Arthur; Chang, Tien-Hsiang; Fu, Hsin-Pin; Yeh, Hsiao-Ping; Hsu, Kuei-Ying; Tsai, Hsin-Ying
Abstract : A review of the literature identifying the critical success factors (CSFs) of project execution revealed two research gaps: a too subjective selection of CSFs rather than an objective selection and too many critical factors, resulting in doubts about their criticality. To overcome these two research gaps, this study proposed a hybrid method that uses the Fuzzy Analytic Hierarchy Process (FAHP) to obtain weightings of factors and ranks their importance. The meaning of criticality, in combination with the concept of acceptable advantage of VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR), was then used to objectively identify the CSFs of project execution, using the environmental consultancy service industry in Taiwan as an example. Finally, six CSFs were found and five management implications were identified, and these findings can serve as a valuable reference for project execution in the environmental consultancy service industry. This combined method can also be used to identify the CSFs of project execution in other fields.